Tiacumicin B: An Antibiotic of Prime Importance and a Natural Product with an Inspiring Complex Structure - Roulland, Emmanuel (Synthesis, 2018)
This short review aims at decrypting and analyzing the various strategies used for the synthesis of tiacumicin B. Natural products synthesis is a way for organic chemists to express inventiveness, intellectual dexterity, and elegance in strategy of synthesis. Some molecular structures are more inspiring than others; and if like tiacumicin B, the architectural challenge meets high biological and medicinal interest, the molecule can then attract the attention of many groups of synthetic chemists.1 Introduction2 The Strategic Challenges of this Total Synthesis3 Construction of the C1–C5 Region4 Construction of the C14–C19 Region5 Construction of the C5–C12 Region6 Construction of the C12–C15 Diene Motif7 Macrocyclization8 Synthesis of the Rhamnosyl Donor9 Synthesis of the Noviosyl Donor and Glycosylation10 The Recurrent Problems Caused by Protective Groups11 Conclusion
Keywords: total synthesis; natural products; antibiotic; metathesis; palladium catalysis; glycosylation